Protective effects of resveratrol against the cardiac developmental toxicity of trichloroethylene in zebrafish embryos. (30th March 2021) - Huang, Yujie; Xia, Ying; Tao, Yizhou; Jin, Hongmei; Ji, Cheng; Aniagu, Stanley; Chen, Tao; Jiang, Yan
Highlights: RSV protected against heart defects in zebrafish embryos exposed to TCE. RSV attenuated TCE-triggered oxidative stress in the heart of zebrafish embryos. RSV attenuated TCE-enhanced cell proliferation in the heart of zebrafish embryos. RSV counteracted TCE-induced AHR activity in the heart of zebrafish embryos. Abstract: Trichloroethylene (TCE), a prevalent environmental contaminant, has been shown to induce cardiac malformations. Resveratrol (RSV) is a natural polyphenolic compound exhibiting protective effects on heart development. To investigate if RSV could protect against TCE-induced heart defects, we exposed zebrafish embryos to TCE (10 ppb) in the presence or absence of RSV (1 μg/mL). Our results showed that RSV significantly attenuated TCE-induced heart defects in zebrafish embryos. The TCE-induced ROS (reactive oxygen species) generation, 8-OHdG (8-hydroxy-2`-deoxyguanosine) formation and cell proliferation were significantly counteracted by RSV. Moreover, RSV attenuated the TCE-induced changes in mRNA expression or activity of genes involved in AHR and Nrf2 signal pathways. We further showed that RSV might inhibit TCE-enhanced cell proliferation by rescuing the downregulation of the p53/p21 axis. In conclusion, our data demonstrates that RSV protects against the cardiac developmental toxicity of TCE by inhibiting AHR activity, oxidative stress and cell proliferation.